The relations between preimage awareness and some other cryptographic properties of hash functions - Anh, Nguyễn Tuấn; Phong, Triệu Quang (Journal of Science and Technology on Information security, 2022)
Abstract— Randomness tests related to overlapping template matching have been proposed in NIST SP 800-22 [1], however the probabilities in these tests are only valid for specific samples and should be recalculated for other samples. In [2], the authors proposed new template matching tests for all 4-bit templates. The new tests can be applied to any sequence of minimum length of 5504 bits whereas the overlapping template matching test in the NIST test suite can only be applied to sequences of minimum length of 106 bits. In this paper, we have modified and proposed new 4-bit template matching tests that can be applied to any sequence of minimum length 3726 bits. Furthermore, we proposed three new 5-bit template matching tests. Our theoretical and practical results show that our new proposed tests are very efficient in psedorandom number generator testing.